A reflection of changing priorities? The reallocative impact of priority‐based budgeting in US municipalities. (30th December 2021) - Mitchell, David; Larson, Sarah E.; Henley, Terry; Spranger, Auria; Myser, Suzette
Abstract: Implemented in over 200 North American local governments, priority‐based budgeting (PBB) reflects a contemporary attempt to systematically determine and implement desired budgetary reallocation. The study utilizes a lagged dependent variable alternative to difference in difference analysis to examine reallocation patterns for 32 early‐adopting US cities before and after PBB implementation. The findings suggest that PBB fulfills its promise, as low‐priority departmental budgetary allocations shrink by 2%–3% following PBB implementation. These PBB early adopters offer evidence that PBB can effectively transcend the marginal, transactional nature of incremental budgeting practices; however, its effectiveness must be weighed against potentially substantial costs of implementation. Applications for Practice: What level of reallocation is necessary to justify a significant and collective organizational effort to alter budgetary and accounting practices? If 4% or above, a wise practitioner should think twice about a head‐first leap into priority‐based budgeting, absent more compelling evidence. The study provides evidence that mere signaling of a move toward priority‐based budgeting implementation can psychologically affect budgetary behavior prior to actual implementation of the approach. The findings also indicate that budgetary reallocation toward higher‐priority departments begins to wane by the third year after priority‐based budgeting is implemented, potentially limiting its long‐term effectiveness.